The Dynamics of Procurement Management: A Complexity Approach - Peter Holm Andreasen (Copenhagen Business School (CBS), 2012)
“How can we understand the dynamics of procurement management?” An answer to this question has predominantly been explained by procurement management experiencing dissatisfaction with the status quo, where the procurement organisation was viewed from other entities in the company as an insignificant, reactive and an administrative part of the business. The potential, however, for the procurement organisation to be significant in the company was argued to be vast (Ammer 1989, Ellram & Carr 1994, Van Weele 2005). In order to change the situation of the procurement organisation, procurement management was informed that they should in gradual steps develop the procurement organisation towards more sophistication and significance (Reck & Long 1988) producing strategies that were aligned with the overall company strategy including the development of policies, procedures, systems, tools and processes (Cousins 2002, Cousins et al 2008). This process changed the perspective of the procurement organisation which among other things, allowed the procurement entity to contribute to the implementation of the concept of supply chain management (Freeman & Cavinato 1990). Ever since I first got familiar with the practices of procurement and its management, I have been puzzled by its complexity. At the same time, I have wondered about how the same space of complexity in the procurement management domain literature has explained the same practices by reductionism, smoothness and simplicity as just described.
hdl:10398/8384
Keywords: 650